THE EFFECT OF THE CHARACTERIZATION OF MAX IN KARAN BAJAJ’S THE YOGA OF MAX’S DISCONTENT - Fanani, Abu; Abdullah, Asep Abbas; Thoriqussud, Muhammad; Mufid, Nur; Amiq (LP3MKIL, 2025)
The purpose of the study is to characterise the main character, Max Pzoras, in Karan Bajaj’s The Yoga of Max’s Discontent. Indeed, the main character's characteristics are unique and poorly portrayed. Therefore, it becomes the attraction of the researcher to study. Using Bogdan’s qualitative approach, the study indicates that the main character, Max, has bad characteristics as follows: emotional, suffering, and indecisive, through which Max undergoes a terrible effect that is traumatic. Then, through the gap in the study, the researcher hopes so much it inspires other researchers to conduct further study in the same novel with different points of view in order that the literary study develop in a significant way.